The Effects of Experimental Sleep Extension in Middle-to-Older-Aged Healthy Sleepers - Alexandria M. Reynolds; Zachary R. Seymour; Imran H. Iftikhar; M. Michele Burnette; Jennifer M. C. Vendemia; Shawn D. Youngstedt (Sleep Science)
Objectives To determine the feasibility for middle-aged and older adults to extend their time in bed by 2 h per night for 3 consecutive weeks. Other aims were to examine the effects of sleep extension on mood, cognitive performance, and cardiovascular health.